Franz Boas : the emergence of the anthropologist - Zumwalt, Rosemary Lévy, 1944- (Critical studies in the history of anthropology., 2019)
"Rosemary Lévy Zumwalt tells the remarkable story of Franz Boas, one of the leading scholars and public intellectuals of the late nineteenth and early twentieth centuries. The first book in a two-part biography, Franz Boas begins with the anthropologist's birth in Minden, Germany, in 1858 and ends with his resignation from the American Museum of Natural History in 1906, while also examining his role in training professional anthropologists from his berth at Columbia University in New York City. Zumwalt follows the stepping-stones that led Boas to his vision of anthropology as a four-field discipline, a journey demonstrating especially his tenacity to succeed, the passions that animated his life, and the toll that the professional struggle took on him. Zumwalt guides the reader through Boas's childhood and university education, describes his joy at finding the great love of his life, Marie Krackowizer, traces his 1883 trip to Baffin Land, and recounts his efforts to find employment in the United States. A central interest in the book is Boas's widely influential publications on cultural relativism and issues of race, particularly his book The Mind of Primitive Man (1911), which reshaped anthropology, the social sciences, and public debates about the problem of racism in American society. Franz Boas presents the remarkable life story of an American intellectual giant as told in his own words through his unpublished letters, diaries, and field notes. Zumwalt weaves together the strands of the personal and the professional to reveal Boas's love for his family and for the discipline of anthropology as he shaped it."--Publisher's description